2021
DOI: 10.1007/s42979-021-00528-5
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Human Sleep Stage Classification Based on Dual Channels of EEG Signal Using Machine Learning Techniques

Abstract: Sleep staging is one of the important methods for the diagnosis of the different types of sleep-related diseases. Manual inspection of sleep scoring is a very time-consuming process, labor-intensive, and requires more human interpretations, which may produce biased results. Therefore, in this paper, we propose an efficient automated sleep staging system to improve sleep staging accuracy. In this work, we extracted both linear and non-linear properties from the input signal. Next to that, a set of optimal featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…The normalization process can not only evaluate the features of the two modalities of EEG and fNIRS on the same scale, but also shorten the data training time to a certain extent. The ReliefF algorithm is a feature weighting algorithm, which assigns different weights to features according to the correlation of each feature and category, and features with a weight less than a certain threshold will be removed The running time of the ReliefF algorithm increases linearly with the increase in the number of samples and the number of original features, so the running efficiency is relatively high (Stamate et al, 2018;Kshirsagar and Kumar, 2021;Satapathy and Loganathan, 2021). In our previous work (Pan et al, 2021), we also confirmed the effectiveness of the ReliefF algorithm for EEG-based multi-modal feature extraction, and it can achieve the effect of feature optimization and feature dimensionality reduction to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…The normalization process can not only evaluate the features of the two modalities of EEG and fNIRS on the same scale, but also shorten the data training time to a certain extent. The ReliefF algorithm is a feature weighting algorithm, which assigns different weights to features according to the correlation of each feature and category, and features with a weight less than a certain threshold will be removed The running time of the ReliefF algorithm increases linearly with the increase in the number of samples and the number of original features, so the running efficiency is relatively high (Stamate et al, 2018;Kshirsagar and Kumar, 2021;Satapathy and Loganathan, 2021). In our previous work (Pan et al, 2021), we also confirmed the effectiveness of the ReliefF algorithm for EEG-based multi-modal feature extraction, and it can achieve the effect of feature optimization and feature dimensionality reduction to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…All classifiers fall under the category of supervised and unsupervised learning. In supervised learning, such as support vector machines (SVM), [59][60][61][62] decision tree (DT), 61,63 random forest (RF), 64,65 and K-nearest neighbor (KNN), 66 the input data is provided along with labelled output data for training the classifier in making accurate predictions. Contrarily, unsupervised learning, such as neural network (NN), [67][68][69][70] involves only the input data provided for training the classifier via the innate differences in feature vectors extracted from the input.…”
Section: Data Processing and Classificationmentioning
confidence: 99%
“…Sleep staging is an essential for diagnosing sleep-related illnesses (Satapathy & Loganathan, 2021). Automated sleep stage scoring aids human and animal sleep analysis since the late 1960s (Grieger et al, 2021).…”
Section: Automated Sleep Stage Scoringmentioning
confidence: 99%